O sujeito nos discursos de resistência em Chico Buarque de Hollanda - Crosara, Franciele Magalhães (2009)
This work consists of a study of songs that belong to the Brazilian dictatorial military period and are popularly known as political songs, once they were used as a vehicle of protest and ideological policy dissemination, consisting of an important resistance instrument to the authoritarian regime. Though, the aim of this research is to verify how the constitution of the subject in the political-social resistance discourse is processed during the military period in Brazil, through parts of the songs by Chico Buarque de Hollanda and, more specifically, verify from which kind of regularities the discursive inscriptions of the military regime emerge and identify regulating principles in the songs. The analysis of the subject constitution, subscribed in a specific social-historical-ideological place, marked by discursive formations that are constitutive to him, helps us not only to have a better subject comprehension, but also of the historical moment and of the discourses the subject was subscribed. Considering that, according to Foucault (1995), the interpretation of the subject is an analysis of the process in which he is subscribed, as he is supposed to be held as an ethical and moral subject, the constitution of the subject in the political-social resistance discourse implies discursive displacements, crossed by the power sphere, according to which power supposes obedience, and by how this complex and heterogeneous net is provided by the determining role of the resistance. Considering the discourse theory based on the assumptions of the French Discourse Analysis, we comprehend that semantic processes are constituted by historical determinations, that everything that is said is historically made possible, and that the search for the social, in the exteriority of the text, crossed by production conditions, by notions of ideology, history, memory and language, constitute inseparable elements to the construction of meaning. One of the discursive regularities found in the process of constitution of the subject and in the construction of meaning was the authorized discourse as a mean of silence.